Trichinella spiralis Calreticulin S-Domain Binds to Human Complement C1q to Interfere With C1q-Mediated Immune Functions - Shao, Shuai; Hao, Chunyue; Zhan, Bin; Zhuang, Qinghui; Zhao, Limei; Chen, Yi; Huang, Jingjing; Zhu, Xinping (Frontiers in Immunology, 2020)
Helminths develop strategies to escape host immune responses that facilitate their survival in the hostile host immune environment. Trichinella spiralis, a tissue-dwelling nematode, has developed a sophisticated strategy to escape complement attack. Our previous study demonstrated that T. spiralis secretes calreticulin (TsCRT) to inhibit host classical complement activation through binding to C1q; however, the C1q binding site in TsCRT and the specific mechanism involved with complement-related immune evasion remains unknown. Using molecular docking modeling and fragment expression, we determined that TsCRT-S, a 153 domain of TsCRT, is responsible for C1q binding. Recombinant TsCRT-S protein expressed in Escherichia coli had the same capacity to bind and inhibit human C1q-induced complement and neutrophil activation, as full-length TsCRT. TsCRT-S inhibited neutrophil reactive oxygen species and elastase release by binding to C1q and reduced neutrophil killing of newborn T. spiralis larvae. Binding of TsCRT-S to C1q also inhibited formation of neutrophil extracellular traps (NET), which are involved in autoimmune pathologies and have yet to be therapeutically targeted. These findings provide evidence that the TsCRT-S fragment, rather than the full-length TsCRT, is a potential target for vaccine or therapeutic development for trichinellosis, as well as for complement-related autoimmune disease therapies.